Typology of Tropical Forest Transition Model in Several Watershed, Sumatera Island - Widyananto Basuki Aryono; Endang Suhendang; I Nengah Surati Jaya; Herry Purnomo (Institut Pertanian Bogor (IPB University), 2018)
At a landscape level, forest transitions have complex spatial heterogeneity characteristics, thus the causes, driving force, typology and specific profile characteristics need to be considered for managing and mitigating forest transition. This paper describes how the diversity of forest transition characteristics was grouped and how the characteristic of group was identified. Typology classes within water catchment areas in Riau, North Sumatera and West Sumatera Provinces, Indonesia were investigated by considering social, economic and biophysical aspects. The main study objective was to develop a forest transition typology at a landscape level. The model typology was derived from a clustering method with the Standardized Euclidean Distance. The study found that the most significant factor which successfully differentiated the typology of forest transition into two typologies was the population growth having approximately 92% of overall accuracy. The first typology (typology 1) could be categorized as rapid forest transition, while the typology 2 was categorized as slow forest transition. The study suggested that the management and mitigation of the impacts of the forest transition should be conducted by considering the landscape typology as a function of the profiles for each typology.